FORMAL MATHEMATICS AND ETHNOMATHEMATICS IN THE PRODUCTION OF URBAN COMMUNITY GARDENS: RATIONALITIES IN ARTICULATION IN THE SANTA ROSA NEIGHBORHOOD, JOSÉ DE FREITAS - Paulo Moreira dos Santos , João; Carlos Rodrigues da Mata, Luis; Clara da Cunha Carvalho, Maria; Rodrigues de Araújo , Gabrielly; Soares dos Santos, Robério; Eduarda Santiago de Araujo, Maria; da Cunha Santiago, Iraneide; Pereira Campos, Edinalva; Gustavo Santiago Santos, José (Journal of Interdisciplinary Debates, 2026)
This article analyzes the mathematical rationalities involved in the production of urban community gardens, focusing on the articulation between formal mathematics, ethnomathematics, and agronomic knowledge. The study problematizes the epistemological hierarchy that privileges formal mathematics over situated mathematical practices commonly used by urban farmers. A qualitative approach was adopted through a case study conducted in the Santa Rosa neighborhood, in the municipality of José de Freitas, Piauí, Brazil. Data were collected through participant observation, semi-structured interviews, and field notes. The findings show that farmers mobilize ethnomathematical knowledge in decisions related to spatial organization, soil management, control of productive time, and commercialization, employing notions of measurement, proportionality, and estimation even without formal symbolic representation. At the same time, limitations of these practices emerge when facing institutional demands for standardization, indicating the need for critical articulation with formal mathematics. The study concludes that integrating different mathematical rationalities broadens the understanding of urban agriculture and presents important implications for mathematics education, rural extension, and the development of public policies that recognize local knowledge.